PHK DAN PANDEMI COVID-19: SUATU TINJAUAN HUKUM BERDASARKAN UNDANG-UNDANG TENTANG KETENAGAKERJAAN DI INDONESIA - Vicko Taniady; Novi Wahyu Riwayanti; Reni Putri Anggraeni; Ahmad Alveyn Sulthony Ananda; Hari Sutra Disemadi (Jurnal Yustisiabel, 2020)
Since the entry of the COVID-19 pandemic in Indonesia in early March 2020, the economy in Indonesia has experienced negative growth. Negative economic growth has resulted in mass layoffs (layoffs) in many companies. The purpose of this study is to analyze mass layoffs during the COVID-19 pandemic which is reviewed from the perspective of the Labor Law. The research method used in this reserach is the normative legal method by prioritizing secondary data. The results of this reserach indicate that termination of employment by many companies hurts workers. Especially in Article 151 paragraph 1 of Law Number 13 of 2003 concerning Manpower, it has been stated that employers, laborers/workers, the government must make every effort to prevent termination of employment. So based on this research it shows that laying off work during the COVID-19 pandemic is not a win-win solution.